AUTHORIAL SYSTEM OF TASKS FOR DEVELOPING THE DIGITAL COMPETENCE OF PROFESSIONAL PRE-HIGHER EDUCATION STUDENTS: CONCEPT AND IMPLEMENTATION EXPERIENCE - Островершенко, А. (SWorldJournal, 2025)
The article presents an authorial system of learning tasks aimed at developing the digital competence of students in professional pre-higher education. The relevance of the study is determined by the need to strengthen the practical component of students’